Landmark trademark cases in China an in-depth analysis - Zhou, Bo; Rui, Songyan; Zhou, Yunchuan; Lin, Xu (Wolters Kluwer, 2017)
"[This book is a] source on Chinese trademark law for non-Chinese intellectual property professionals with its...descriptions and analyses of twenty-six landmark cases located in the context of the overarching system. For fifteen consecutive years, China has received and processed more trademark filings than any other country; the number of trademarks filed in China in 2015 alone was three times that of the combined trademark filings made in the United States (second place) and the European Union (third place)...[Topics covered include:] absolute and relative grounds of trademark registrability; dual-track system of administrative enforcement and judicial protection; well-known trademark protection; defenses in trademark infringement cases; damage determination in a trademark infringement lawsuit; third party's prior rights; personal name similarity; resolution mechanism for conflicts and disputes; time limit to challenge a trademark assignment; and trademark squatting. The analysis of each case...illustrates how trademarks are acquired, maintained, cancelled, invalidated, and protected in China. Prior to diving into these cases, an introductory chapter provides a brief history of China's trademark system and describes the three amendments to the Trademark Law (1993, 2001, and 2013) and the impact made by each."--
Keywords: Recht; Trademarks / Law and legislation / China / Cases; Trademarks / Law and legislation; China; Trials, litigation, etc